Pengaruh Motivasi Karir, Dorongan Finansial, Persepsi Mengenai Biaya Pendidikan Terhadap Minat Mahasiswa Mengikuti Pendidikan Profesi Guru - Rosida, Nila; Rochmawati, Rochmawati (Jurnal Pendidikan Akuntansi (JPAK), 2024)
This research aims to find out how career motivation, financial encouragement, and perceptions regarding educational costs influence Accounting Education students' interest in participating in Teacher Professional Education. This research uses a quantitative research design using primary data sources taken directly by researchers with a Likert scale questionnaire. A purposive sampling technique was chosen to be used in this research and 98 students majoring in Accounting Education class of 2017 at Surabaya State University were the sample. The multiple regression analysis method was used to analyze the data obtained. The research results show that; (1) Career motivation has a significant effect on students' interest in participating in PPG, high career motivation will encourage students to improve their abilities so they can achieve higher careers and positions, one of which is by obtaining teacher certification. (2) Financial encouragement has a significant effect on students' interest in participating in PPG, the higher the student's financial encouragement, the higher their interest in participating in PPG. (3) Perceptions regarding education costs do not influence students' interest in participating in PPG, different economic conditions are not always directly proportional to students' interest in participating in PPG. (4) Career motivation, financial encouragement, student perceptions regarding educational costs can simultaneously influence students' interest in pursuing professional teacher education.